2022
DOI: 10.3389/fendo.2022.986565
|View full text |Cite
|
Sign up to set email alerts
|

Potential therapeutic role of pyroptosis mediated by the NLRP3 inflammasome in type 2 diabetes and its complications

Abstract: As a new way of programmed cell death, pyroptosis plays a vital role in many diseases. In recent years, the relationship between pyroptosis and type 2 diabetes (T2D) has received increasing attention. Although the current treatment options for T2D are abundant, the occurrence and development of T2D appear to continue, and the poor prognosis and high mortality of patients with T2D remain a considerable burden in the global health system. Numerous studies have shown that pyroptosis mediated by the NLRP3 inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 226 publications
0
7
0
Order By: Relevance
“…NLRP3 inflammasomes have been profoundly attributed to the pathogenic mechanisms that induce T2DM and its related complications. 49 Ding et al revealed that NLRP3 inflammasome modulates endoplasmic reticulum stress, which regulates glucose tolerance, insulin resistance, inflammation and apoptosis in adipose tissue in DM. 190 It seems that the activation of NLRP3 inflammasome leads to the maturation and the release of pro-inflammatory mediator IL-1β in the sciatic nerve of diabetic rats.…”
Section: Role Of Pyroptosis-related Signaling Pathways In the Progres...mentioning
confidence: 99%
See 1 more Smart Citation
“…NLRP3 inflammasomes have been profoundly attributed to the pathogenic mechanisms that induce T2DM and its related complications. 49 Ding et al revealed that NLRP3 inflammasome modulates endoplasmic reticulum stress, which regulates glucose tolerance, insulin resistance, inflammation and apoptosis in adipose tissue in DM. 190 It seems that the activation of NLRP3 inflammasome leads to the maturation and the release of pro-inflammatory mediator IL-1β in the sciatic nerve of diabetic rats.…”
Section: Role Of Pyroptosis-related Signaling Pathways In the Progres...mentioning
confidence: 99%
“… 232 Recent evidence suggests that overactivation of NLRP3 inflammasome plays an essential role in the pathogenesis of DM and its complications. 49 , 123 , 190 , 233 , 234 The NLRP3 inflammasome includes the apoptosis-associated speck-like adaptor protein (ASC), NLRP3 and pro-caspase-1. Upon activation, NLRP3 becomes ligated to ASC and then binds to pro-caspase-1.…”
Section: Inhibition Of Pyroptosis-dependent Signaling Pathways For Th...mentioning
confidence: 99%
“…In response to different stimuli, cells undergo different types of cell death, which modulates the survival of β-cells during disease progression. Apoptosis is the predominant mechanism associated with β-cell loss in Type 1 diabetes and a reduced β-cell population in Type 2 diabetes 119 122 . In Type 1 diabetes, β-cell failure is mediated by an immune response characterized by mononuclear and T cells interacting with antigen-presenting cells to generate a high level of inflammatory cytokines, chemokines, and other triggering factors, leading to apoptotic cell death.…”
Section: Diseases Associated With Mitochondrial Cell Deathmentioning
confidence: 99%
“…A report showed that necroptosis was the previously unknown mechanism underlying β-cell death in response to islet amyloid formation. NLRP3 inflammasome-mediated pyroptosis also appears to contribute significantly to the development of Type 2 diabetes and insulin resistance 122 . The activation of the NLRP3 inflammasome can be induced by various factors, such as high glucose, fatty acids, ROS, and IAPP levels 127 , 128 .…”
Section: Diseases Associated With Mitochondrial Cell Deathmentioning
confidence: 99%
“…Since NLRP3 can sense pathogens and many stimuli derived from the host, abnormal NLRP3 inflammasome activation is demonstrated to be an essential driver of a series of complex human diseases, including acute kidney injury, atherosclerosis, non-alcoholic steatohepatitis (NASH), and type 2 diabetes (Li et al 2022a , b ; Wang et al 2021 ; Yang et al 2022 ; Zhao et al 2021 ), suggesting that NLPR3 inflammasome may act as a potential therapeutic target for these diseases (Chauhan et al 2020 ; Wang and Hauenstein 2020 ). Therefore, inhibiting NLRP3 inflammasome may be a promising approach for treating NLRP3-mediated inflammatory diseases (Chiazza et al 2016 ; Pappritz et al 2022 ; Swanson et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%